Risk Factors for Obstetric Anal Sphincter Injuries among Women Delivering at a Tertiary Hospital in Southwestern Uganda - Mahad Ali; Richard Migisha; Joseph Ngonzi; Joy Muhumuza; Ronald Mayanja; Jolly Joe Lapat; Wasswa Salongo; Musa Kayondo (Hindawi Limited, 2020)
Background. Obstetric anal sphincter injuries (OASIS) arise from perineal trauma during vaginal delivery and are associated with poor maternal health outcomes. Most OASIS occur in unattended deliveries in resource-limited settings. However, even in facilities where deliveries are attended by skilled personnel, a number of women still get OASIS. Objectives. To determine the incidence and risk factors for obstetric anal sphincter injuries among women delivering at Mbarara Regional Referral Hospital (MRRH). Methods. We conducted an unmatched hospital-based case control study, with the ratio of cases to controls of 1 : 2 (80 cases and 160 controls). We defined a case as a mother who got a third- or fourth-degree perineal tear after vaginal delivery while the controls recruited were the next two mothers who delivered vaginally without a third- or fourth-degree perineal tear. A questionnaire and participants' medical records review were used to obtain sociodemographic and clinical data. We estimated the incidence of OASIS and performed univariable and multivariable logistic regression to identify the associated risk factors. Results. The cumulative incidence for OASIS during the study period was 6.6%. The risk factors for OASIS were 2nd stage of labour ≥1 hour (aOR 6.07, 95%CI 1.86-19.82, p=0.003), having episiotomy performed during labour (aOR 2.57, 95%CI 1.07-6.17, p=0.035), perineum support during delivery (aOR 0.03, 95%CI 0.01-0.12, p<0.001), and monthly income of >50,000 shillings (aOR 0.09, 95%CI 0.03-0.28, p<0.001). Conclusions and Recommendations. The risk factors for obstetric anal sphincter injury were prolonged second stage of labour and performing episiotomies during deliveries while higher monthly income and perineum support during delivery were protective. We recommend routine support to the perineum during delivery. Care should be taken in mothers with episiotomies, as they can extend and cause OASIS.